2015
DOI: 10.1002/micr.22403
|View full text |Cite
|
Sign up to set email alerts
|

A “no‐touch‐technique” in mandibular reconstruction with reconstruction plate and free flap transfer

Abstract: The results of our study showed that our no-touch-technique may be a safe and effective procedure for the prevention of perioperative plate-related complications for mandibular reconstruction with an MRP and free flap transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…MRP has become less frequently performed because its wound complication rate is significantly higher than that of VBG . However, short‐term results of mandibular reconstruction with MRP have greatly improved with recent advances in reconstructive techniques . Also in the present study, no major plate‐related problems requiring plate removal occurred in the short term.…”
Section: Discussionmentioning
confidence: 49%
“…MRP has become less frequently performed because its wound complication rate is significantly higher than that of VBG . However, short‐term results of mandibular reconstruction with MRP have greatly improved with recent advances in reconstructive techniques . Also in the present study, no major plate‐related problems requiring plate removal occurred in the short term.…”
Section: Discussionmentioning
confidence: 49%
“…A recent study from Davies et al 22 demonstrated that optimizing contouring of reconstruction plates to bone reduces the odds of plate exposure. Fujiki et al 23 suggest a “no-touch-technique” for mandibular plates that prevents contamination by saliva and leads to significantly lower rates of plate-related infection and fistula formation. One alternative to the fibula free flap is the lateral scapular border or scapular tip free flap, which allows for more robust soft tissue coverage of hardware compared to the skin and soft tissue of the lower extremity.…”
Section: Discussionmentioning
confidence: 99%
“…5 Microsurgical free flaps are now considered state of the art in head and neck reconstruction following head and neck cancer surgery. 5,6 Although some adjunctive postoperative wound care has been proposed to prevent postoperative infections, reduce flap complications, and promote wound healing, [7][8][9] determining how to reduce postoperative wound infections and surgical morbidity remains highly challenging for surgeons.…”
Section: Introductionmentioning
confidence: 99%